41.2k views
0 votes
Can someone help me out with this question? How do you use the Pythagorean theorem to answer b?

Can someone help me out with this question? How do you use the Pythagorean theorem-example-1

2 Answers

6 votes

Answer:

UN = 7

Explanation:

Using Pythagoras' identity on the right triangle.

The square on the hypotenuse is equal to the sum of the squares on the other 2 sides, that is

(4x - 3)² = (3x + 3)² + x² ← distribute both sides

16x² - 24x + 9 = 9x² + 18x + 9 + x² ← simplify

16x² - 24x + 9 = 10x² + 18x + 9 ( subtract 10x² + 18x + 9 from both sides )

6x² - 42x = 0 ← factor out 6x from each term

6x(x - 7) = 0

Equate each factor to zero and solve for x

6x = 0 ⇒ x = 0

x - 7 = 0 ⇒ x = 7

However, x > 0 ⇒ x = 7

Hence UN = x = 7 and SU = 4x - 3 = (4 × 7) - 3 = 28 - 3 = 25

User Jayadratha Mondal
by
5.8k points
3 votes

Answer:

Explanation:

Can someone help me out with this question? How do you use the Pythagorean theorem-example-1
Can someone help me out with this question? How do you use the Pythagorean theorem-example-2
User PoliceEstebi
by
5.8k points